Ecologia de Athene cunicularia (Molina 1782) (Aves, Strigidae) no litoral centro-norte de Santa Catarina, Brasil - Rocha, Alana Drielle (2020)
Athene cunicularia (Molina, 1782) is a bird of prey that inhabits much of the Americas. The studies related to this species provide subsidies for the planning and management of environments direct at the preservation of avifauna species, since birds of prey can be used as indicators of the degree of conservation of ecosystems, futhermore it is an important functional role in natural ecosystems acting in the population control of insects and rodents. Aiming to deepen the ecological knowledge about A. cunicularia and understanding that knowledge about the relationship of species with their habitat is important for their conservation, this work developed a population study of the species in four dune areas on the coast of Santa Catarina, the beaches of Interpraias, Navegantes, Barra Velha and Praia Brava and led to the elaboration of three chapters. The first followed the population fluctuation in the beaches over three years and brought information about biometric measurements of the specimens captured between the four coastal regions of Santa Catarina. The second work presented the behavioral categories of owls during the course of the day and analyzed the influence of the environment on the owl's alarm responses when approaching humans. Finally, in the third chapter, the burrowing owl diet in the studied areas was analyzed and compared according to the surroundings. Considering the three studies, it is concluded: 1 - Owls have biometries similar to the subspecies described for the region and their population tends to decrease with increases in disturbances in the region where it is inserted. 2 - The owl has several similar behaviors throughout the day, however, the night time proved to be the main one for its feeding, also, it has difference in the responses to the approach in the studied regions, a possible consequence of the urbanized environment. 3 - The burrowing owl is generalist and opportunistic in its feeding, as it feeds on the abundant items in the regions where they are inserted, from invertebrates to small vertebrates, however it showed significant differences between its choices in the sampled sites. Therefore, the burrowing owl, A. cunicularia, is a species that has adapted to the urban environment, but disturbances can still impair the species success in several regions. The results presented here show great local dependence of A. cunicularia for feeding resources and natural areas for breeding. Future conservation of the environment in which they are inserted are essential for this species persistence.